Formulation and characterization of mupirocin nanomicelles in insulin-based gel for dermatological application - Maysaa B Zubairi; Abdulkareem H Abd; Mohammed S Al-lami (Wolters Kluwer Medknow Publications, 2023)
Aim: To produce and analyze mupirocin nanomicelle (MP-NM) in insulin-based gel. Procedures: MP-NM was prepared using solvent evaporation with Tween 80 as a surfactant. HPMC polymer prepared gel. MP-NM was characterized by globular diameter, polydispersity index (PDI), pH, entrapment efficiency (EE), and transmission electron microscopy (TEM). NM MP release was studied in vitro. Results: The revolutionary MP-NM in insulin-based gel dissolves MP completely without precipitation due to its unique physical and chemical properties. MP had 8.64 ± 0.2 nm globular diameter, high EE (98.85 ± 0.01%), and normal homogeneous dispersion (PDI, 0.143 ± 0.003) in NM. MP's formula showed rapid first-order kinetics release. Conclusion: To our knowledge, this is the first MP-NM nano-drug delivery system employing insulin-based gel. It has promising pre-clinical and clinical uses.